(untitled) (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES RESEARCH AND DEVELOPMENT (IJSSRD), 2024)
The Government of Andhra Pradesh has established Rythu Bazaars in the year 1999 for the empowerment of farmers, who are selling their agricultural produce, especially the vegetables and fruits directly to the customers without interference of middlemen. This study aims to investigate the impact of Rythu Bazaars on the socio-economic status of these farmers. In this purpose the study selected East Godavari district in Andhra Pradesh state as study area and the selective six Rythu Bazaars in the six major cities in the district are study units. From each Rythu Bazaar 20 farmers were selected for the data collection. These farmers regularly bring the vegetables/fruits to these markers from their fields and sell directly to the consumers without interference of middlemen. Thus, the findings of this study revealed that a predominant group of farmers observed impact of Rythu Bazaars found more on their social status, household income and their nutritional food habits. Whereas a significant number of farmers expressed that they could increase their household savings and financial status with reducing their household debts. This leads to increase their land holdings and household assets. Thus it is found that the overall impact of Rythu Bazaars on socio-economic aspects of the farmers found positive significance on their socio-economic status.